2020
DOI: 10.1108/ecam-06-2019-0319
|View full text |Cite
|
Sign up to set email alerts
|

Social sustainability considerations in construction project feasibility study: a stakeholder salience perspective

Abstract: PurposePast research recommends integration of social sustainability (SS) considerations in construction project feasibility study for benefitting a larger group of project stakeholders. However, there is a lack of empirical evidence to this effect, especially from the developing economies. The purpose of this study is to address this knowledge gap through a SS-centric analysis of feasibility study reports using a stakeholder salience perspective.Design/methodology/approachFeasibility study reports for 61 proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 87 publications
(126 reference statements)
1
27
0
Order By: Relevance
“…This need is also shared by some of the papers we investigated. For example, on the topic of social sustainability in India, Goel et al (2020) argue for extending their template of analysis to "similar studies in context of other developing economies undergoing a similar socio-economic transition" (p. 1449). Thus, developing economies deserve closer attention, while large scale studies could help compare cross-cultural settings and operationalizations of ethically driven stakeholder management.…”
Section: Discussion and Implications For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This need is also shared by some of the papers we investigated. For example, on the topic of social sustainability in India, Goel et al (2020) argue for extending their template of analysis to "similar studies in context of other developing economies undergoing a similar socio-economic transition" (p. 1449). Thus, developing economies deserve closer attention, while large scale studies could help compare cross-cultural settings and operationalizations of ethically driven stakeholder management.…”
Section: Discussion and Implications For Future Researchmentioning
confidence: 99%
“…The findings from this review highlighted a dominance of conceptual articles. The need for novel empirical research has been highlighted by many authors (Bourne et al, 2019;Constandt et al, 2019Constandt et al, , 2020Goel et al, 2020;Wagner-Tsukamoto, 2019), highlighting the need for good solid empirical studies that report the way stakeholders see the world.…”
Section: Implication 3: Getting Scholars Out Of Their Ivory Towersmentioning
confidence: 99%
“…Ismail [41] studied the implementation of PPP projects in Malaysia and found that good governance, fulfillment of contracts, and a good market and legal environment were critical for project success. Goel et al [42] applied the social network analysis method to analyze the relationship between stakeholders, pointing out that construction workers, communities, public individuals, and end users were all stakeholders of the project. Stakeholders have conflicting interests and concerns, which may devastate the project if mismanaged.…”
Section: Stakeholders In Water Ppp Projectsmentioning
confidence: 99%
“…To be specific, economic sustainability means that the project can bring stable investment returns in its life-cycle, and that is can have a positive impact on local economic development [47]. Social sustainability refers to the improvement of public goods and services for the public, more employment opportunities, and development potential for the local region in which the project is being conducted [42]. Ecological sustainability means that a balance has been achieved between the ecological system and the natural system, ensuring intergenerational equity of the environment [48].…”
Section: Critical Factors On Sustainability Of Water Ppp Projectsmentioning
confidence: 99%
“…These skills complement each other and make it easier for the professional to work effectively in multidisciplinary groups during the development of construction projects [7][8][9]. With the rapid growth of sustainable development, there has been a growing demand for social sustainability to be included into the AEC industry [10,11]. Social sustainability covers social considerations of the final user and health and safety issues of the project team [12,13]; therefore, social sustainability is associated to the management practices that includes employee skills training (BIM education program, information communication technologies, teamwork, among others) [10].…”
Section: Introductionmentioning
confidence: 99%